Income inequality and physical and mental health: testing associations consistent with proposed causal pathways. Issue 6 (12th May 2006) - Zimmerman, Frederick J; Bell, Janice F
Abstract : Objectives: To test associations between individual health outcomes and ecological variables proposed in causal models of relations between income inequality and health. Design: Regression analysis of a large, nationally representative dataset, linked to US census and other county and state level sources of data on ecological covariates. The regressions control for individual economic and demographic covariates as well as relevant potential ecological confounders. Setting: The US population in the year 2000. Participants: 4817 US adults about age 40, representative of the US population. Main outcome measures: Two outcomes were studied: self reported general health status, dichotomised as "fair" or "poor" compared with "excellent", "very good", or "good", and depression as measured by a score on the Center for Epidemiologic Studies depression instrument >16. Results: State generosity was significantly associated with a reduced odds of reporting poor general health (OR 0.84, 95%CI: 0.71 to 0.99), and the county unemployment rate with reduced odds of reporting depression (OR 0.91, 95%CI: 0.84 to 0.97). The measure of income inequality is a significant risk factor for reporting poor general health (OR 1.98, CI: 1.08 to 3.62), controlling for all ecological and individual covariates. In stratified models, the index of social capital is associated with reduced odds of reporting poor general health among black people and Hispanics (OR 0.40, CI: 0.18 to 0.90), but not significant among white people. The inequality measure is significantly associated with reporting poor general health among white people (OR 2.60, CI: 1.22 to 5.56) but not black people and Hispanics. Conclusions: The effect of income inequality on health may work through the influence of invidious social comparisons (particularly among white subjects) and (among black subjects and Latinos) through a reduction in social capital. Researchers may find it fruitful to recognise the cultural specificity of any such effects.